Glycerol carbonate as a fuel additive for a sustainable future. Issue 10 (20th June 2018) - Szőri, Milán; Giri, Binod Raj; Wang, Zhandong; Dawood, Alaaeldin E.; Viskolcz, Béla; Farooq, Aamir
Abstract : Glycerol carbonate can be a promising fuel or a promising soot-reducing fuel additive for a sustainable future. Abstract : Policy-makers and researchers have been considering a shift from conventional fossil fuels to renewable sources due to the growing concerns over global warming and diminishing oil reserves. Biodiesel, a renewable bio-driven fuel, can be derived from vegetable oils and animal fats, and is considered to be bio-degradable, non-toxic and environmentally friendly. The cetane number and calorific power of biodiesel are quite similar to those of conventional diesel. Crude glycerol of about 10–20% by volume appears as a byproduct in biodiesel production. The increasing demand for biodiesel has led to a substantial increase of glycerol supply in the global market and a dramatic fall in the price of glycerol which has warranted alternative uses of glycerol. One potential way to deal with the crude glycerol overflow is to convert it to glycerol carbonate (GC) and use GC as a fuel or fuel additive. Prior studies have indicated that carbonate esters can significantly reduce particulate emissions during engine combustion. In this work, we have explored possible reaction pathways in the initial stage of glycerol carbonate pyrolysis. Ab initio /RRKM-master equation methods are employed to differentiate various reaction pathways and to obtain the pressure- and temperature-dependence of the major channels. We have found that glycerol carbonate decomposes almost exclusively to produce CO2 and 3-hydroxypropanal over 800–2000 K and radical forming channels are unimportant. As 3-hydroxypropanal is one of the main products of GC decomposition, and aldehydes are known to have a very high impact on soot reduction, we conclude that GC has great potential for cleaner combustion as a fuel additive.